Healthy, wealthy and wise? A review of the wider benefits of education - Grant Johnston (New Zealand Government, The Treasury, 2004)
This paper reviews evidence that a greater education causes better outcomes in life, over and above the effects of having a higher-paying job. Comparatively little has been written which draws together evidence on the wider (that is, wider than just earnings-related) benefits of education, although studies which ignore these benefits might considerably underestimate the total return from a additional year of education or an additional qualification. Research suggests that increased education, as measured by the time people spend in formal education or the qualifications they attain, may cause a reduction in cigarette smoking, anxiety disorders, anti-social disorders, suicide, crime, teenage pregnancies, unemployment and reliance on welfare benefits, at least when these outcomes are measured in young adulthood. Education may also have an effect on people's health. The wider benefits of education are difficult to quantify, however, and the degree of uncertainty around them is considerable. Policy-makers would be unwise to rely too heavily on the existence of wider benefits when making decisions about public investment in education.
Keywords: I21; I31; 330; education; returns to education; returns to schooling; wider benefits; social benefits; socio-economic determinants